Measurements of Gasification Characteristics of Coal and Char in CO2-Rich Gas Flow by TG-DTA - Zhigang Li; Xiaoming Zhang; Yuichi Sugai; Jiren Wang; Kyuro Sasaki (Journal of Combustion)
Pyrolysis, combustion, and gasification properties of pulverized coal and char in CO2-rich gas flow were investigated by using gravimetric-differential thermal analysis (TG-DTA) with changing O2%, heating temperature gradient, and flow rate of CO2-rich gases provided. Together with TG-DTA, flue gas generated from the heated coal, such as CO, CO2, and hydrocarbons (HCs), was analyzed simultaneously on the heating process. The optimum O2% in CO2-rich gas for combustion and gasification of coal or char was discussed by analyzing flue gas with changing O2 from 0 to 5%. The experimental results indicate that O2% has an especially large effect on carbon oxidation at temperature less than 1100°C, and lower O2 concentration promotes gasification reaction by producing CO gas over 1100°C in temperature. The TG-DTA results with gas analyses have presented basic reference data that show the effects of O2 concentration and heating rate on coal physical and chemical behaviors for the expected technologies on coal gasification in CO2-rich gas and oxygen combustion and underground coal gasification.